Regionalization Jequetepeque River Basin the method of grouping and the Regional Vector - Guerrero Pérez, Diana María
In this work the precipitation of 14 rain gauge was analyzed from 1966 to 2006, in the Jequetepeque River Basin (Peru), allowing the regionalization of the precipitation and characterization of rainfall patterns, using the method of combining group analyzing the main components. It was achieved to determine rainfall patterns in the river basin areas where there is no information using the Regional Vector Method. In the southern of the river basin, lower precipitation (452–512mm) compared to the north (859 – 930mm) was observed, it has been a significant impact of the mountain range in this region. This methodology may be applied in Colombia given the lack of hydrological stations and missing data information.